Bovine cysticercosis and human taeniasis in a rural community in Ethiopia. (19th June 2020) - Gutema, Fanta D.; Shiberu, Teferi; Agga, Getahun E.; Abdi, Reta D.; Hiko, Adem; Tufa, Takele B.; Hailu, Yacob
Abstract: Background: Bovine cysticercosis is a worldwide zoonotic disease that affects cattle caused by the larval stage of the tapeworm Taenia saginata, the adult parasite that causes taeniasis in humans. Although bovine cysticercosis, and the associated human taeniasis, is controlled in developed countries, it is one of the neglected tropical diseases. Like other parts of Ethiopia, raw or undercooked beef consumption is common in the rural community of Yem district with no meat inspection services. Methods: We conducted an abattoir survey to estimate the prevalence of bovine cysticercosis in cattle and a questionnaire survey to determine the level of historical human taeniasis infection in Yem district of Ethiopia. Results: Bovine cysticercosis was detected in 3.1% of 485 cattle examined. Although animal level prevalence was low, a subset of positive animals had a higher rate of cysticercosis infection widely distributed in various parts of the body. Over two‐fifths (40%) of the cysts were found in the tongue making it an important organ to look for during meat inspection. Over half of the cysts were viable indicating their potential to infect people. History of taeniasis was reported by 71.5% of 151 residents interviewed during the study. Raw meat consumption was very common (89.4%) among the residents; people who consumed raw meat were 25 times more likely to report taeniasis than those who did not. In addition, traditional treatments using herbs and chemicals of unknown efficacy and risk were very common. Conclusions: Bovine cysticercosis and human taeniasis are important in this rural community. Providing meat inspection services and public health education on intervention measures such as proper cooking of meat, access to latrines and clean water are effective strategies that can break the lifecycle of the parasite and ensure beef safety and public health.